Trance and Dance in Bali (1951). On the Musical Selections of Mead and Bateson’s Film - Suryanegara, I (Revue musicale OICRM, 2022)
This article discusses the soundtrack used for the ethnographic film Trance and Dance in Bali made by anthropologists Margaret Mead and Gregory Bateson in 1951. The soundtrack consists of a selection of Balinese gamelan and voice pieces, recorded by the labels Odeon and Beka in 1928, and chosen and arranged by Colin McPhee to fit the on-screen action. The film depicts a reenactment of a calonarang ceremony, a ritual which takes place in villages in Bali during the night, consisting in a sacred dance-drama that is highly regionally specific in its execution. However, for the purposes of Mead and Bateson, this calonarang was performed outside its ritual context in order to provide footage for the ethnographers. The aim of this article is to determine the original source of the soundtrack, discuss what is presented visually in the film, assess the adequacy (or inadequacy) of the choices of music in relation to the image, and in the case of inadequacy, to provide suggestions for musical alternatives. The musical and ritual regionalisms inherent to Balinese musical and ritual practice render some of the soundtrack choices inadequate. We argue that the chosen pieces do not all appropriately support the calonarang performance and ceremony depicted, due to inaccurate musical and ritual regionalisms.